1974
DOI: 10.1055/s-0028-1099399
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOCHEMICAL INVESTIGATION OFTHYMELEA HIRSUTA

Abstract: 1. The unsaponifiable matter of the lipids o f Thymelea hirsuta was investigated and the following substances were separated: a) Hydrocarbon fraction, proved by GLC and MS analyses to be a mixture o f n-C2,, n-Cze, n-Cze, n-CJo and n-C3,. Separation of the individual n-alkanes was achieved by preparative GLC. 6 ) T w o alcohol fractions, proved by GLC and MS to be mixtures of octacosanol, hexacosanol, tetracosanol and docosanol. One of the two fractions corresponds to that previously reported as an unidentifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While antioxidant status such as G-S-transferase, catalase and TAC enzymes revealed significant differences among treatments and control. Likewise, [48] and [49] showed that the TAC of 13S powdered was efficient to avoid oxidations in the quail. A few research examined the effects of BSO, SSO, RSO, and their combination as independent dietary supplements, so the scarcities of researches to compare our results with them in Japanese quail.…”
Section: Blood Parametersmentioning
confidence: 98%
“…While antioxidant status such as G-S-transferase, catalase and TAC enzymes revealed significant differences among treatments and control. Likewise, [48] and [49] showed that the TAC of 13S powdered was efficient to avoid oxidations in the quail. A few research examined the effects of BSO, SSO, RSO, and their combination as independent dietary supplements, so the scarcities of researches to compare our results with them in Japanese quail.…”
Section: Blood Parametersmentioning
confidence: 98%